The unheard prayer : religious toleration in Shakespeare's drama - Sterrett, Joseph. (Studies in Religion and the Arts, 2012)
Titus shoots his arrows bearing petitions for justice to the gods; Claudius asks 'what form of prayer can serve my turn?'; Lear wishes he could crack the vault of heaven with his prayers. Again and again, Shakespeare dramatises the scenario of the unheard prayer, in which the one who prays does so full well in the knowledge that no one is listening, interested, or even there at all. The scenario is keyed to the anxieties that surrounded the act of praying itself, so full as it was with controversy, the centrepiece of sectarian dispute over what was good and bad religion. This study reads the unheard prayer scenario as itself an appeal for a vision of tolerance, unobtainable perhaps, but nevertheless desired and imagined.